Empowering teamwork activities through inspiration, motivation and action in blended learning environment - Mokhtar, Makhfudzah; Wan Adnan, Wan Azizun (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
This paper shares about the use of blended learning in empowering teamwork activities among students via three main elements namely inspiration, motivation and action. Firstly students are presented with videos related to team work as their inspiration, followed by a motivational session, discussing the most important aspects that they should have to be the best team members. The next phase is their action in realizing the assignment given. It starts with some light activities like online games, followed by summative assessment. Students' perceptions on the activities are very encouraging and it is expected that better spirit of teamwork among the students could be achieved.